Writing for Electronic Media - Champagne, Brian (Open textbook library., 2017)
Welcome to Writing for Electronic Media, an OER textbook. OER stands for Open Educational Resource, which means it’s free for all who access. Since it is electronic, I will do what I can to keep it updated with the changing media. People’s viewing habits are changing as they migrate to mobile sources, social media, and kitten videos.Television News is still a dominant #1 source, and radio is still the safest way to stay informed in your car. Hopefully, you already have some journalism background. This book does not teach the who, what, when, where, why, and how of reporting; its goal is to teach how to present the journalism you already know via electronic media, primarily television.